2021
DOI: 10.1177/14651165211064485
|View full text |Cite
|
Sign up to set email alerts
|

Bargaining power in informal trilogues: Intra-institutional preference cohesion and inter-institutional bargaining success

Abstract: Informal trilogue meetings are the main legislative bargaining forum in the European Union, yet their dynamics remain largely understudied in a quantitative context. This article builds on the assumption that the negotiating delegations of the European Parliament and the Council play a two-level game whereby these actors can use their intra-institutional constraint to extract inter-institutional bargaining success. Negotiators can credibly claim that their hands are tied if the members of their parent institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Finally, the models contain a control variable capturing the distance of the Commissioner responsible for the draft proposal from the Commission median to take into account that extreme positions could matter more if they are held by the lead Commissioner. In addition, I control for the number of Commissioners present in the CoC, for the preference heterogeneity in the EP and the Council (using data shared by Haag (2022)), as well as measures for the distance between the Commission median and the median in the other legislative chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the models contain a control variable capturing the distance of the Commissioner responsible for the draft proposal from the Commission median to take into account that extreme positions could matter more if they are held by the lead Commissioner. In addition, I control for the number of Commissioners present in the CoC, for the preference heterogeneity in the EP and the Council (using data shared by Haag (2022)), as well as measures for the distance between the Commission median and the median in the other legislative chambers.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to their relevance for the EP's legislative organization, several studies have demonstrated that rapporteurs tend to be quite successful in shaping legislative outcomes in their favor (Costello and Thomson, 2010; Costello and Thomson, 2011). Especially in the informal setting of inter-institutional trilogues, rapporteurs are often able to wield substantial policy influence (Brandsma and Hoppe, 2021; Haag, 2022). Moreover, even though their draft reports are subject to an open amendment rule at the committee level of the EP, the rapporteur position is only rarely challenged successfully by competing amendments (Hurka, 2013).…”
Section: Introductionmentioning
confidence: 99%